The Application of Appropriate Technology for Basreng Crackers Dough Mixer Machine for Home Industry Development - Erlyna Wida Riptanti; Kusnandar Kusnandar; Isti Khomah; Raden Rara Aulia Qonita (PRIMA: Journal of Community Empowering and Services, 2022)
Basreng crackers are fried meatball crackers produced by Small and Medium Enterprises (SME) Sumber Rejeki and are named Kripik Basreng. Basreng is a cracker made from tapioca flour, noodles, and eggs. The problem faced by Sumber Rejeki SME’s that if the SME produces in a large capacity, the kneading process takes a long time and the ingredients used are not mixed evenly. This activity aims to introduce dough machines in SME Sumber Rejeki. The method is participatory by involving SME Sumber Rejeki, starting from the need identification stage, design, and machine introduction. As a result of these activities, the community service team succeeded in realizing a dough kneading machine under the needs and desires of SME Sumber Rejeki. This machine can increase time efficiency by about 80-90% and reduction of labor operating costs by IDR 2,000/prescription processing. The process of making dough is only one-sixth time per recipe compared to without using a machine. This process has an impact on the workforce being able to do other jobs so that they are more productive. This condition affects increasing the production capacity of basreng up to 400% per day and improving the dough quality. The side effect is good business management to production basreng more efficient than previous and fulfilled the demand quickly.